Marriage in the western Church : the christianization of marriage during the patristic and early medieval periods. - Reynolds, Philip Lyndon 1950- (Leiden Brill, 1994)
Marriage in the Western Church examines how marriage acquired a specifically Christian identity in the Western Church from the patristic through Carolingian periods. It shows how theologians came to regard marriage as an ecclesiastical institution and how they developed a Christian theology of marriage. [publisher's description]
Keywords: Marriage -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600; Marriage -- Religious aspects -- Christianity -- History of doctrines -- Middle Ages, 600-1500; #GOSA:II.P.AU.3; 241.64*4 -- Theologische ethiek: partnerkeuze en huwelijk; 265.5 -- Huwelijk